Impact of a course of injections with melatonin on morphological and functional changes in the optic nerve in experimental animals with hypopinealism - O.V. Nedzvetska; U.A. Pastukh; O.V. Kuzmina de Gutarra; I.V. Pastukh; I.A. Soboleva; N.M. Sotnyk (Ukrainian Society of Ophthalmologists, 2023)
Background: Optic atrophy (OA) may be expected in hypopinealism, which is accompanied by degenerative changes in the retina. Purpose: To assess the impact of a course of injections with melatonin on the morphological and functional optic nerve (ON) changes in rabbits exposed to prolonged around-the-clock light (ATCL) leading to hypopinealism. Material and Methods: Eighty-four rabbits were used in this experimental study. Group 1 (an ATCL group) was composed of 32 animals exposed to ATCL to develop functional hypopinealism. Group 2 (an ATCL+M group) was composed of 29 animals exposed to ATCL but treated with intramuscular melatonin for 14 days. Group 3 (a control group or CG) was composed of 23 intact animals maintained under natural day/night cycle conditions. Groups were subdivided into subgroups based on experimental constructs (1-2 months, 3-5 months, 8-12 months, 18-19 months, 26-28 months). Blood melatonin levels were assessed by commercially available enzyme-linked immunosorbent assay kits. ON specimens were obtained and comprehensively assessed morphologically and morphometrically. Results: Night-time blood melatonin level in experimental groups was almost six-fold lower than that in controls. Signs of abnormal ON circulation were observed at ≤12 months of ATCL exposure. ON demyelination was observed from months 3-5 of the experiment. Sclerotic and atrophic processes in the ON were observed at 28 months of ATCL exposure. In ATCL26-28 and ATCL+M26-28 subgroups, the mean relative vascular area in the intraorbital ON was significantly reduced compared to CG26-28 (2.01 ± 0.15% and 1.93 ± 0.15%, respectively, versus 3.20 ± 0.13%, р < 0.05). In addition, the mean relative area of the perivascular connective tissue (4.80 ± 0.15% and 4.61 ± 0.17%, respectively) was significantly increased compared to CG26-28 (3.40 ± 0.14%, р < 0.05). Moreover, the mean diameter of the nerve fiber bundle (2.51 ± 0.09 ×10-6 m and 2.73±0.10×10-6 m, respectively) was significantly reduced compared to CG26-28 (3.85±0.14×10-6 m; р < 0.05). Conclusion: The morphological findings (like demyelination of nerve fibers and thinning of nerve fiber bundles of the ON), combined with low blood flow in ON vessels, vascular wall thickening and connective tissue growth, indicated the development of sclerotic atrophy of the ON, in the presence of marked melatonin deficiency, in rabbits exposed to ATCL. The 14-day course melatonin treatment of ATCI-exposed rabbits exerted anti-edematous effects at early time points (< 5 months), until obviously irreversible changes in the ON occurred. However, the course melatonin treatment exerted no impact on the development of OA in animals with persistent, marked hypopinealism developed in the presence of prolonged (28-month) exposure to ATCI.